2005
DOI: 10.1103/physrevb.71.132513
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory dynamics of a superconductor vortex lattice in high amplitude ac magnetic fields

Abstract: In this work we study by ac susceptibility measurements the evolution of the solid vortex lattice mobility under oscillating forces. Previous work had already shown that in YBCO single crystals, below the melting transition, a temporarily symmetric magnetic ac field (e.g. sinusoidal, square, triangular) can heal the vortex lattice (VL) and increase its mobility, but a temporarily asymmetric one (e.g. sawtooth) of the same amplitude can tear the lattice into a more pinned disordered state. In this work we prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Moreover, this effect may be enhanced by the presence of different resonant frequencies for different vortices in the lattice, depending upon their position with respect to the pinning array. An ideal technique to perform this experiment, in addition to AC magnetotransport, is frequency-dependent AC susceptibility [193].…”
Section: Frequency Dependence Of Periodic Pinningmentioning
confidence: 99%
“…Moreover, this effect may be enhanced by the presence of different resonant frequencies for different vortices in the lattice, depending upon their position with respect to the pinning array. An ideal technique to perform this experiment, in addition to AC magnetotransport, is frequency-dependent AC susceptibility [193].…”
Section: Frequency Dependence Of Periodic Pinningmentioning
confidence: 99%
“…sawtooth) becomes less mobile [5]. Moreover, mobility is also reduced if a temporarily symmetric AC field forces vortices into large excursions [9]. Probably, the repeated interactions between neighbors facilitates the healing of topological defects, while temporarily asymmetric AC fields or large vortex excursions promote their creation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In ac susceptibility experiments, the PE is observed as an anomalous increase in shielding capability or a decrease in losses, also usually interpreted as an anomalous decrease in VL mobility. Recent experiments in YBCO crystals, have shown that the mobility of the VL increases after assisting the system with a symmetric ac field (or current) [31] of moderate amplitude [34]. On the other hand, when vortices are assisted by an asymmetric ac field, the VL becomes less mobile [31].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments in YBCO crystals, have shown that the mobility of the VL increases after assisting the system with a symmetric ac …eld (or current) 30 of moderate amplitude 31 . On the other hand, when vortices are assisted by an asymmetric ac …eld, the VL becomes less mobile 30 .…”
Section: Introductionmentioning
confidence: 99%